A new insight into catalytic role of copper sulfate on elemental mercury oxidation: DFT and experimental study. (15th September 2019) - Yang, Shu; Liu, Kang; Liu, Min; Yan, Xu; Liu, Cao; Wen, Minneng; Liu, Hui; Chai, Liyuan
Graphical abstract: Highlights: Hg 0 oxidation by HCl on copper sulfate catalyst was first investigated by DFT. Experimental results confirmed negative effect of crystal water on copper sulfate. CuSO4 /α-Al2 O3 showed >90% Hg 0 oxidation efficiency in HCl and O2 at 250–400 °C. Hg 0 oxidation over CuSO4 /α-Al2 O3 catalyst follows the Eley-Rideal mechanism. Abstract: Copper sulfate (CuSO4 ) is a ubiquitous component in natural minerals and industrial dusts. However, CuSO4 has been believed usually that it has adverse effect on elemental mercury (Hg 0 ) removal from flue gas. Here, we offered a new insight into the effect of crystal water in copper sulfate on Hg 0 catalytic oxidation. The structure evolution of copper sulfate by density functional theory (DFT) calculation revealed anhydrous CuSO4 crystal contributing to a better HCl adsorption which provided a precondition for Hg 0 oxidation. Experimental results about the catalytic activity sequence of CuSO4  > CuSO4 ·H2 O > CuSO4 ·5H2 O with HCl confirmed the negative effect of crystal water on Hg 0 catalytic oxidation. To realize industrial application, supported catalysts CuSO4 /α-Al2 O3 synthesized by wet impregnation method was employed for elemental mercury (Hg 0 ) oxidation and the results exhibited excellent performance in Hg 0 oxidation under 250 °C–400 °C. The Hg 0 conversion efficiency was above 97% in the presence of 2 ppm HCl + 6% O2 at 300 °C. Combining computational and X-ray photoelectron spectroscopy (XPS) analyses together, Cu atoms exposure on the surface of anhydrous CuSO4 were the critical active sites for Hg 0 oxidation and the reaction obeyed the Eley–Rideal mechanism.